Hubungan Usia dan Tingkat Pendidikan dengan Kejadian Anemia Pada Ibu Hamil Trimester III - Putri, Amelia; Sulastri, Sulastri; Hariyanti, Reni; Puspita Sari, Aninda Ayu Putri (Lontara Journal of Health Science and Technology, 2025)
In 2017, there were 295,000 women who died during pregnancy and after childbirth. The aim of this study is to determine the prevalence of anemia in third-trimester pregnant women in the working area of Talang Bakung Community Health Center and its relationship with age and education level. The methodology of this research is quantitative with a retrospective approach. The target population of this study is all pregnant women at Puskesmas Thalang Bakung, totaling 146 individuals. The sampling method used is total sampling. Data analysis used univariate and bivariate analysis with statistical testing using the chi-square test. The results of the research conducted showed that the analysis using the Chi-Square statistical test indicated that the factors related to anemia are age (p=0.015) and education level (p=0.001) with the prevalence of anemia at Puskesmas Talang Bakung. Therefore, it can be concluded that there is a relationship between age and education level with the prevalence of anemia at Puskesmas Talang Bakung, and it is hoped that pregnant women should pay more attention to their health during pregnancy, especially the intake of iron nutrients from food and supplements.